The Comparison Between Palm Oil Processing Productivity in PTPN V PKS Tandun and PT.Hutahaean - Fransisco Carlos Sampayo S Carlos (Jurnal Agribisnis, 2022)
Perkebunan Nusantara V (PTPN V) Tandun and PT. Hutahaean are agricultural companies that have Palm Oil Mill (PKS) with same capacity of 45 tons / hour.PKS Tandun processes FFB that produced from PTPN V’s own plantation with an area of ​​7314.92 hectares. Meanwhile PKS Hutahaean also has its own plantation with an area of ​​4614 hectares that processes not only its own FFB but also from the local community plantations.The Differences in FFB supply, processing hours, and the use of other inputs have resulted in differences of the palm oil and palm kernel production.This made differences in PTPN V productivity This study aims to analyze the productivity of palm oil processing and to analyze the superior productivity of palm oil processing between PTPN V PKS Tandun and PT. Hutahaean.The productivity analysis technique uses the Marvin E. Mundel method by measuring partially and totally the depreciation, material, energy, labor and maintenance inputs from January 2016 to December 2017.The partial productivity measurement shows that PKS Tandun has the highest partial productivity index at energy input, labor and maintenance.However, the measurement of total productivity shows that the highest total productivity index in PKS Hutahaean is better and tends to be higher and more stable. The factor affecting the total productivity index is the application of the palm oil processing management system that has been applied.